Antioxidant enzymes in chickpea colonized by Piriformospora indica participate in defense against the pathogen Botrytis cinerea. Issue 1 (December 2017) - Narayan, Om; Verma, Nidhi; Singh, Alok; Oelmüller, Ralf; Kumar, Manoj; Prasad, Durga; Kapoor, Rupam; Dua, Meenakshi; Johri, Atul
Abstract Piriformospora indica, a root endophytic fungus, promotes growth of the economically important chickpea plant (Cicer arietinum Linn.) and protects it against the pathogenic fungusBotrytis cinerea . Biomass and root development were found to be significantly improved in chickpea plants colonized withP .indica as compared to the plants grown withoutP .indica as well as from the plants infected with theB .cinerea . Our PCR analyses showed that gradual increase in the colonization ofP .indica in the plants result in the inhibition of the colonization ofB .cinerea .P .indica colonized plants showed increased antioxidant enzyme activities. Interestingly, there were pronounced decrease in the antioxidant enzyme activities in shoots infected withB .cinerea and colonized withP .indica in alternate and simultaneous mode as compared to plants infected withB .cinerea alone. We conclude thatP .indica helps plants to overcome the disease load by enhancing antioxidant enzyme defense system. Our data suggest that, bio-protective action ofP .indica might be mediated via systemic induction of antioxidant defense in the host plants.